2016
DOI: 10.1039/c5nr08634e
|View full text |Cite
|
Sign up to set email alerts
|

High-speed detection of DNA translocation in nanopipettes

Abstract: We present a high-speed electrical detection scheme based on a custom-designed CMOS amplifier which allows the analysis of DNA translocation in glass nanopipettes on a microsecond timescale. Translocation of different DNA lengths in KCl electrolyte provides a scaling factor of the DNA translocation time equal to p = 1.22, which is different from values observed previously with nanopipettes in LiCl electrolyte or with nanopores. Based on a theoretical model involving electrophoresis, hydrodynamics and surface f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…31 The speed of the DNA during the process is determined by electrophoresis and hydrodynamic friction, in some cases potentially also involving surface adsorption effects. 32,33,34 For sensing purposes not just the average properties of the translocation signal, such as the mean translocation time ‹t› or the mean current modulation I, are relevant, but equally the corresponding distributions. It is illustrative to discuss these aspects in a little more detail, inasmuch they inform experimental design and sensor operation.…”
Section: Fundamental Aspects Of the Dna Translocation Processmentioning
confidence: 99%
“…31 The speed of the DNA during the process is determined by electrophoresis and hydrodynamic friction, in some cases potentially also involving surface adsorption effects. 32,33,34 For sensing purposes not just the average properties of the translocation signal, such as the mean translocation time ‹t› or the mean current modulation I, are relevant, but equally the corresponding distributions. It is illustrative to discuss these aspects in a little more detail, inasmuch they inform experimental design and sensor operation.…”
Section: Fundamental Aspects Of the Dna Translocation Processmentioning
confidence: 99%
“…Silicon based nanomaterials are suitable for device applications, since they feature excellent bio-compatibility and bio-degradability. 21 These properties make silica a key material in wet technologies concerned with water desalination, 6 biosensing, 21 detection of macromolecules [22][23][24] or the separation of chemicals. 5 Experimental and molecular simulations studies have shown that silica nanopores influence the structure and dynamics of confined water.…”
Section: Introductionmentioning
confidence: 99%
“…The probability distribution of e was found to be skewed and well approximated heuristically by a log-normal distribution. 16 Sub-events are more challenging to identify and analyse, because they typically contain far fewer data points than the events themselves. We therefore took a somewhat different approach in searching for and analysing those sub-events.…”
Section: Methodsmentioning
confidence: 99%